2021
DOI: 10.1007/s11033-021-06341-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aflibercept and arsenic trioxide on the proliferation, migration and apoptosis of oral squamous cell carcinoma in vitro

Abstract: A ibercept and arsenic trioxide drugs apply a cytotoxic effect on some human cancer cell lines. However, no more study has followed the effects of both drugs, especially arsenic trioxide, on oral squamous cell carcinoma (OCC). We used three OCC lines as a model to show the effect of these drugs on the genetically complex disease and investigate its targeted therapy.In this study, three human OCC cell lines were used from different patients. We treated cell lines with both medications to detect the effect and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…However, As 2 O 3 is widely used in clinical cancer treatment, in which reactive oxygen species levels are increased, thus leading to cell death ( 38 ). An in vitro study by Derakhshan et al revealed the cytotoxic effect of As 2 O 3 on oral squamous cell carcinoma ( 39 ). Therefore, we speculated that the role of As may vary in different cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…However, As 2 O 3 is widely used in clinical cancer treatment, in which reactive oxygen species levels are increased, thus leading to cell death ( 38 ). An in vitro study by Derakhshan et al revealed the cytotoxic effect of As 2 O 3 on oral squamous cell carcinoma ( 39 ). Therefore, we speculated that the role of As may vary in different cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…However, the recurrence possibility of the treatment is around 7%-13% in residual tumor and 15%-58% in advanced stage tumor [ 4 ]. It is highly believed that the drug resistance could be the main reason for the failure in obtaining desirable treatment outcomes [ 2 , 5 ]. Hence, new treatment strategies and medicines are needed to cope with the growing concerns of worst survival rate.…”
Section: Introductionmentioning
confidence: 99%